X=5(x-6)-10+1

Simple and best practice solution for X=5(x-6)-10+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X=5(x-6)-10+1 equation:



X=5(X-6)-10+1
We move all terms to the left:
X-(5(X-6)-10+1)=0
We calculate terms in parentheses: -(5(X-6)-10+1), so:
5(X-6)-10+1
We add all the numbers together, and all the variables
5(X-6)-9
We multiply parentheses
5X-30-9
We add all the numbers together, and all the variables
5X-39
Back to the equation:
-(5X-39)
We get rid of parentheses
X-5X+39=0
We add all the numbers together, and all the variables
-4X+39=0
We move all terms containing X to the left, all other terms to the right
-4X=-39
X=-39/-4
X=9+3/4

See similar equations:

| 6y+5=7y−5 | | 72=5-5y | | 8x+6=-2x | | -5x–2x=63 | | 45-p=28 | | 0.05/x+9=16 | | 8w^2-12w+(4w-5)+6= | | x+56=95x+56=95 | | 9x=-27.2 | | -5(7n-2)=-20 | | 3(x-5)=0.5(6x-12) | | x/4.5=17 | | 8k+13=101 | | -3(-3x-5)=-25-x | | 2x^2=924 | | 6.4k+7-2.1k=32.8 | | x/7.3=17 | | 2h/3+5=-7 | | 4(a-3)=4 | | A=2n-7 | | 4(2x+1)-2x=8+4(x+5) | | 3(4−x)−(2x+3)=5+3(x−4) | | x/9.7=13 | | 4x+1-(2x+1)=3x-(2x-4)-x | | (6x+17)=(7x+-3) | | 12x+18=13x-14 | | 9(4-v)=-4(v+6) | | 27-2x=-1 | | 57=2x | | 6x-28=2x+4(1-3x) | | 13x+5=10x+9 | | 36=h^2-2h |

Equations solver categories